2008
DOI: 10.1007/s11199-007-9372-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Rape Myths in Headlines and Their Effects on Attitudes Toward Rape

Abstract: The present research investigated the prevalence and effects of rape myths in newspaper headlines. In study 1, a content analysis of online news headlines from US media (N=555) surrounding the 2003-2004 Kobe Bryant sexual assault case showed that 10% endorsed a rape myth. In study 2, students at a mid-sized university in the midwestern USA (N=154) read headlines endorsing or not endorsing rape myths. Male participants exposed to mythendorsing headlines were (a) less likely to think Bryant was guilty than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 48 publications
0
87
1
Order By: Relevance
“…Finally, in a content analysis, it was found that newspaper headlines containing rape myths promote rape-supportive attitudes in readers (Franiuk, Seefelt, & Vandello, 2008); a notion that has profound consequences, as stereotypical portrayals in newspapers can help in justifying the perpetrators' acts (Ward, 1995).…”
Section: New Methodologiesmentioning
confidence: 99%
“…Finally, in a content analysis, it was found that newspaper headlines containing rape myths promote rape-supportive attitudes in readers (Franiuk, Seefelt, & Vandello, 2008); a notion that has profound consequences, as stereotypical portrayals in newspapers can help in justifying the perpetrators' acts (Ward, 1995).…”
Section: New Methodologiesmentioning
confidence: 99%
“…Myths about rape persist among both men and women, although rape myth acceptance tends to be higher amongst men than women. It is suggested that women's acceptance and endorsement of rape myths is due to a belief in the control of victimisation; that is, if they do the 'right' thing and behave in a 'good' way, then they will not be sexually victimised (Bohner et al 2002;Franiuk, Seefelt and Vandello 2008). Men's endorsement of rape myths, it has been argued, may also occur not for misogynist reasons but because it allows men to distance themselves from rapists who are deemed 'monsters' or 'beasts' (Franiuk et al 2008: 791).…”
Section: Rape Myths and Their Acceptancementioning
confidence: 99%
“…Therefore, discourses about sexual violence in the media tend to enact rather than counter traditional rape myths about the role of the victim and perpetrator in the criminal act (Greer 2003;O'Hara 2012;Sela-Shayovitz 2015). Research indicates that print, radio and television media are more inclined to blame victims for their sexual assaults (Franiuk et al 2008), and sexual violence is the only crime where pre-trial publicity tends to bias jurors against the victim, not the defendant (Mullin, Imrich and Linz 1996). As with the criminal justice system the most commonly endorsed myth is that the victim is lying (Franiuk et al 2008).…”
Section: Rape Myths and Their Acceptancementioning
confidence: 99%
See 2 more Smart Citations